Gender-Based Wage Differences: The Effects of Occupation and Job Segregation in Israel - Gattiker, Urs E.; Cohen, Aaron (Relations industrielles / Industrial Relations, 1997)
A study examines gender differences in the process governing salary disparity between typically female occupations and typically male occupations. The findings indicate that choice of occupation does affect income disparity. The study provides evidence of pay discrimination against men in predominantly female occupations and against women in female- and male-dominated positions. Women did not experience a positive effect by being employed in the public sector, nor did either of the genders working in larger organizations. The implications of the findings for the generalizability of human capital, structural and institutional theories explaining wage disparity in a cross-national context are discussed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Gender; Labor Unions; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wage differential; Wages & salaries